Calibration and design of the E and B EXperiment (EBEX) cryogenic receiver - Zilic, Kyle Thomas (2014)
University of Minnesota Ph.D. dissertation. August 2014. Major: Physics. Advisor: Professor Shaul Hanany. 1 computer file (PDF); ix, 144 pages. I discuss the design, construction, and calibration of the E & B EXperiment (EBEX), a balloon-borne telescope designed to measure the B-mode polarization anisotropy of the cosmic microwave background (CMB). EBEX observes the sky with 8 arcmin resolution in three frequency bands centered on 150, 250, and 410 GHz, with over 1,500 detectors. Polarimetry is performed through use of a continuously rotating achromatic half-wave plate with fixed wire-grid polarizer. The experiment was designed to detect the gravitational-lensed B-mode signal and detect or set an upper limit for the inflationary B-mode signal. In this thesis, I describe the design and structure of various subsystems of the EBEX receiver and predict their experimental performance. Several calibrating instrumental response experiments are described and the results reported and compared to predictions. A brief review of the 2012-2013 long duration balloon (LDB) flight from McMurdo Station, Antarctica, is provided and a summary of the receiver performance during flight characterized.